Problems of the equilibrium of a rigid body and mechanical systems - Do, Sanh; Do, Khoa Dang (Computer Assisted Methods in Engineering and Science, 2017)
In this article one of the greatest generalized methods for establishing the equilibrium equations of a rigid body and the set of rigid bodies is proposed. It is related to six equations of moments of force about six the edges of a reference tetragon. It is possible to obtain different alternatives by substituting the force moment-equation for the force project-equation. Four different forms of equilibrium are established. It is important writing equilibrium equations of bodies possible to apply the special software as Mathcad, Maple.